Manifestation of the Book of Tobit in the Homily of Raphael - Woldehana, Wondwosen Admasu; Assefa, Abba Daniel (Universitas PGRI Madiun, 2024)
The focal point of this piece of writing is to manifest the reception of the Book of Tobit in the homily of Raphael. The archangel Raphael appears for the first time in Tobit. The earliest attestation of the Book of Tobit goes back to 3rd century B.C. The text is attested in the Greek version of the Old Testament called Septuagint. On the other hand, the homily of Raphael is part of the 15th C hagiography, one of the religious books in EOTC tradition. This study investigates the use of the material found in the Book of Tobit in the Dersana Rufaýel as reflected in the traditional Ethiopian spiritual practice and worship. There was a significant influence of the homily of Raphael in Ethiopian tradition. It has two different versions: one attributed to John Chrysostom and the other one is to Abuna Zecharyas. Now The Haiq Estifanos Manuscript has close connection with Book of Tobit and represents the version of Abuna Zecharyas. The Title of the manuscript is “Dǝrsanä Rufaýel” and it was found in the Monastery of Haiq Estifanos [Haiq ýÉstifanos Gädam] under the title of Dǝrsanä Mälaýǝkt which is additional. The study compares this homily with the similar contents in Book of Tobit. The archangel Raphael who appears for the first time in Tobit (3rd century B.C.) and was written by a Jew of the Diaspora, probably in Egypt is attested in the following verses Tb. 12:15). (Tb. 5:13; 7:7), (6:1-3); 6:14; 8:3) and (11:7-14). The narration of Haiq Estifanos Manuscript relied heavily on the book of Tobit especially from Book of Ţobit Chapter five to fifteen. , The study analyses the Homily of Raphael by distinguishing between quotations and allusions to the Book of Tobit. , After the background, the study will discuss the quotations and the allusions of the book of Tobit in the Homily of Saint Raphael. The analysis shows that the therapeutic and salutary role played by the Archangel Raphael in the Book of Tobit is also found in the homily of Saint Raphael. One thus discovers the impact of the Book of Tobit on Dǝrsanä Rufaýel and the role of the latter on Ethiopian Spiritual practice and worship.